Analysis of Clinical Practice of Mental Nursing Supportive Therapy on Emotional Control of Patients at Risk of Violent Behavior - Sultan Risdian Abi; Safitri, Linda Dwi Novial (Promotion and Prevention in Mental Health Journal, 2025)
Patients with mental disorders are often brought to the emergency room of mental hospitals in a fixated condition that begins with violent behavior that can endanger themselves, the environment and the surrounding people. This study aims to analyze mental nursing with supportive therapy for patients at risk of violent behavior in the Punai room of Atma Husada Mahakam Samarinda Mental Hospital. The method used in this research is descriptive with a nursing approach. The subjects of this case study were patients with a risk of violent behavior as many as 2 people selected with inclusion and exclusion criteria in accordance with the Evidence Based Nursing journal. The results of the analysis showed a significant change from SLKI, starting with a scale of 2 increasing enough to turn into a scale of 5 decreasing, also supported by measurement with the RUFA Intensive III Score scale (21-30). This can be applied by room nurses to patients with violent behavior as a method of changing behavior in clients.